“Uma peça muito preciosa de significado ainda desconhecido” - António Conduto Oliveira (Medievalista)
In spite of the frequency with which it appears in 15th century documentation, the Portuguese term "gibanete" remains vague and problematic. The aim of this article is to define exactly what a "gibanete" is, what piece of armament it corresponds to, and what implications this definition might have for the study of military equipment in 15th century Portugal. This research will make use of both Portuguese and foreign sources from the 14th to 16th centuries, allowing us to compare how these pieces evolved in Portugal vis-a-vis their European counterparts. It will be complemented by contemporary Portuguese and foreign studies which will allow for systematising and sorting this piece in the general framework of late medieval Portuguese armaments and in the broader context of late medieval European armour.